Transcriptome analysis of Ophiocordyceps sinensis before and after infection of Thitarodes larvae. Issue 6 (June 2016) - Zhong, Xin; Gu, Li; Li, Shao-song; Kan, Xu-tian; Zhang, Gu-ren; Liu, Xin
Abstract: Ophiocordyceps sinensis, also referred to as the Chinese caterpillar fungus, is a rare entomopathogenic fungus found in the Qinghai–Tibetan Plateau that is used as a traditional Chinese medicine. O. sinensis parasitizes the larvae of the ghost moth Thitarodes . Characterization of the transcriptome of O. sinensis before and after host infection may provide novel insight into the process by which the fungus interacts with Thitarodes and may help researchers understand how to sustain this valuable resource. In this study, we performed RNA-sequencing (RNA-seq) using Illumina HiSeqTM 2000 technology to generate gene expression profiles of two developmental stages of O. sinensis . Thread-like hyphae before infection and yeast-like hyphal bodies after infection of host larvae were collected for transcriptome analysis. We found that 1640 genes were differentially expressed ( q -value < 0.05), of which 818 were upregulated (49.878 %) and 822 were downregulated (50.122 %). Gene ontology (GO) analysis revealed that the differentially expressed genes (DEGs) were especially enriched in terms associated with Biological Process and Molecular Function. Several genes encoding transporter and permease proteins, three glycoside hydrolases, two mycotoxin-related proteins, an antigen protein, and an allergen were identified as being significantly up- or downregulated. Collectively, our findings provide a novel resource for understanding O. sinensis during two critical developmental stages, and offer the opportunity to further investigate the functional mechanisms underlying these stage-specific molecular differences. Highlights: Gene expression profiles of two developmental stages of Ophiocordyceps sinensis were compared. 1640 genes were differentially expressed between two critical developmental stages. 29 genes were screened as the most significantly upregulated genes. 17 genes were screened as the most significantly downregulated genes.